Connecting Taiwan
1 online resource (240 pages)
Keywords: Taiwan has often been characterised as an isolated society in its search for sovereignty and security. Its contact with the world in an era of globalization and post-modernity, however, has increasingly led to Taiwanese actors successfully participating in many regional and global fields.